C-reactive protein and haemoglobin level in acute kidney injury among preterm newborns - Fiva Aprilia Kadi; Tetty Yuniati; Yunia Sribudiani; Dedi Rachmadi (Medicinski glasnik, 2021)
Aim: To explore the possibility of C-reactive protein (CRP) and haemoglobin (Hb) in prediction and risk assessment of acute kidney injury (AKI) among preterm newborns. This is believed to be closely related to the incidences of AKI, and could be the most affordable in early detection of AKI. Methods: A case control study was carried out at Dr Hasan Sadikin Hospital in Bandung with a total of 112 preterms divided into two groups: with and without AKI based on the neonatal KDIGO (Kidney Disease: Improving Global Outcomes). CRP and creatinine serum were measured within 6 hours and at 72-96 hours after birth. The routine blood count included haemoglobin, haematocrit, leucocyte, and thrombocyte in the first 24 hours of life. Results: CRP increase was the most influential factor for AKI with sensitivity of 80.6% and specificity of 60.2%. An increase in CRP >0.04 had an aOR (95% CI) of 5.64 (1.89-16.84). Haemoglobin <14.5 g/dL had slightly increased aOR (95% CI) of 1.65 (1.05- 8.63) Conclusion: CRP increases >0.04 and level Hb <14.5 g/dL showed acceptable as an early warning for AKI in preterm newborns.
Keywords: AKI; anaemia; CRP; neonates; renal injury